Analisis Risiko Kesehatan dan Keselamatan Kerja Pada Kegiatan Produksi Tower di PT Kunango Jantan Padang - Fitriyani; Zella Engelya Otiva; Veri Wardi (HEALTH CARE : JURNAL KESEHATAN, 2021)
Each work environment has a source of danger and potential hazards that can arise in the work area. PT Kunango Jantan is one of the large factories that produce towers in West Sumatra. This study aims to analyze the risks in the tower production section of PT. Kunango Male in 2020. The design of this study was qualitative using the HIRARC method with AS / NZS 4360: 2004 calculations. This research took place from August 2019 - June 2020. The techniques used in data collection were interviews, observation, and document review. Informants selected as many as 10 people using purposive sampling techniques. Hazard identification results obtained from the source of danger comes from transportation equipment, machinery and unsafe actions of workers in each production area. The risk assessment of the production section is divided into 1 very high risk, 22 high risk, 2 moderate risk and 4 mild risk. The controls that have been applied are the use of PPE, engine inspection, installation of signs, first aid kit and APAR. There are 4-9 sources of danger at each stage of production. Assessments at each stage of production are generally high risk. Risk control has not been carried out properly, so it is recommended to companies to improve OHS enforcement in the work environment and conduct routine monitoring of workers.